An enemy of the people. - Ibsen Henrik (Easter African Educational, 2007)
Arena Stage, Zelda Fichandler, producing director, Thomas C. Fichandler, executive director presents in the Arena "An Enemy of the People," by Henrik Ibsen, English version by John Patrick Vincent, acting version for Arena Stage by Zelda Fichandler, directed by Zelda Fichandler, settings by Grady Larkins, costumes by Marjorie Slaiman, lighting by Hugh Lester, technical director Henry R. Gorfein, George Touliatos, associate producer.